2016
DOI: 10.1073/pnas.1610150113
|View full text |Cite
|
Sign up to set email alerts
|

Disease resistance through impairment of α-SNAP–NSF interaction and vesicular trafficking by soybean Rhg1

Abstract: α-SNAP [soluble NSF (N-ethylmaleimide–sensitive factor) attachment protein] and NSF proteins are conserved across eukaryotes and sustain cellular vesicle trafficking by mediating disassembly and reuse of SNARE protein complexes, which facilitate fusion of vesicles to target membranes. However, certain haplotypes of the Rhg1 (resistance to Heterodera glycines 1) locus of soybean possess multiple repeat copies of an α-SNAP gene (Glyma.18G022500) that encodes atypical amino acids at a highly conserved functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
158
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(167 citation statements)
references
References 55 publications
9
158
0
Order By: Relevance
“…It has been reported that the interaction of two or more alleles (epistasis) plays a major role in an organism's resistance to diseases and pests (Bayless et al ., ; Meksem et al ., ; Nagel, ). The rhg1 GmSNAP18 protein interacts with NSF (N‐ethylmaleimide–sensitive factor) protein and disturbs vesicle trafficking (Bayless et al ., , ). We discovered that soybean germplasm provided a wide range of SCN resistance controlled by natural variants (SNP and CNV) at both the rhg1 and Rhg4 loci.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the interaction of two or more alleles (epistasis) plays a major role in an organism's resistance to diseases and pests (Bayless et al ., ; Meksem et al ., ; Nagel, ). The rhg1 GmSNAP18 protein interacts with NSF (N‐ethylmaleimide–sensitive factor) protein and disturbs vesicle trafficking (Bayless et al ., , ). We discovered that soybean germplasm provided a wide range of SCN resistance controlled by natural variants (SNP and CNV) at both the rhg1 and Rhg4 loci.…”
Section: Discussionmentioning
confidence: 98%
“…A recent report suggests that the rhg1 a-SNAP confers resistance by cytotoxic effects of the large-scale accumulation of the aberrant a-SNAP protein at the nematode feeding sites, which disrupts SNARE complexes and vesicle trafficking (Bayless et al, 2016). How GmSHMT08 conditions this process is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms of how SNAP proteins mediate SCN resistance remain unclear. Recently, it has been described that elevated expression of resistance-type Rhg1 α-SNAP negatively affected the abundance of SNARE-recycling 20 S complexes, disrupting vesicle trafficking, and induced elevated abundance of NSF causing cytotoxicity27. However, expression of other loci encoding a canonical wild-type α-SNAPs counteracted the cytotoxicity of resistance-type Rhg1 α-SNAP27.…”
mentioning
confidence: 99%
“…Recently, it has been described that elevated expression of resistance-type Rhg1 α-SNAP negatively affected the abundance of SNARE-recycling 20 S complexes, disrupting vesicle trafficking, and induced elevated abundance of NSF causing cytotoxicity27. However, expression of other loci encoding a canonical wild-type α-SNAPs counteracted the cytotoxicity of resistance-type Rhg1 α-SNAP27. Furthermore, a SCN gene encoding a bacterial-like protein containing a putative SNARE domain (HgSLP-1), an esophageal-gland protein that is secreted by the nematode during plant parasitism, has been suggested to physically interact with the Rhg1 α-SNAP in SCN resistance28.…”
mentioning
confidence: 99%